2018
DOI: 10.1002/sem3.20115
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Literature: The Needs of Nontraditional Students in Postsecondary Education

Abstract: Nontraditional students, or adult learners, are the new majority in the classroom in any sector of higher education according to the National Center for Education Statistics. These students are considered nontraditional if they identify with at least one of the following criteria: be at least 25 years old, attend school part-time, work full-time, be a veteran, have children, wait at least one year after high school before entering college, have a GED instead of a high school diploma, being a fi rst-generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 8 publications
1
38
0
Order By: Relevance
“…Moreover, this study suggests student financial aid knowledge among adults may be contingent upon income: wealthier adults may know more about the financial aid process than peers. Extant research has demonstrated adult students may be the neediest students on campus, given the living expenses incurred by adults (Carter, 2018;Fairchild, 2003;Kasworm et al, 2009;Levine & Nidiffer, 1996;MacDonald, 2018;Prins et al, 2015;Ziskin et al, 2014). Similarly, this study finds prospective adults in lower socioeconomic levels may be the neediest in terms of financial wellness programming and student financial aid knowledge.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Moreover, this study suggests student financial aid knowledge among adults may be contingent upon income: wealthier adults may know more about the financial aid process than peers. Extant research has demonstrated adult students may be the neediest students on campus, given the living expenses incurred by adults (Carter, 2018;Fairchild, 2003;Kasworm et al, 2009;Levine & Nidiffer, 1996;MacDonald, 2018;Prins et al, 2015;Ziskin et al, 2014). Similarly, this study finds prospective adults in lower socioeconomic levels may be the neediest in terms of financial wellness programming and student financial aid knowledge.…”
Section: Resultssupporting
confidence: 55%
“…The National Center for Education Statistics (NCES, 2018) reported between 2001 and 2015, US higher education experienced a 35% increase in enrollment of postsecondary students aged 25-34. Between 2015 and 2016, the NCES predicted an 11% increase of postsecondary students aged 25-34 (NCES, 2018), as many adult learners have decided to pursue a degree due to career changes, requisite job training, a desire to earn a higher salary, and a wide variety of other influences (Carter, 2018;MacDonald, 2018;NCES, 2018;Patterson, 2018;Prins, Kassab, & Campbell, 2015;Smith-Barrow, 2018). Chen (2017) and MacDonald (2018) asserted adult learners aged 25-34 have comprised over 33% of the total postsecondary enrollment in the US for over a decade, yet researchers have consistently found adult learners to be an under-supported and under-researched population of postsecondary students in the United States (Carter, 2018;Chen, 2017;MacDonald, 2018;Osam, Bergman, & Cumberland, 2017;Rogers, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students—graduate and undergraduate—experience numerous difficulties and obstacles that may be unknown or unfamiliar to colleagues and mentors. Some students, for example, may have obligations and responsibilities that are obscure to faculty and mentors (MacDonald, 2018). To address some of these complexities, mentors can, for instance, be flexible in scheduling meetings with students who may not be able to adhere to a rigid weekly schedule.…”
Section: Framing Your Research and Teaching Mind‐setmentioning
confidence: 99%
“…It has been well‐studied that understanding and anticipating the needs of unique student populations can help educators develop strategies to engage and sustain nontraditional learners 11 . However, despite the problematic attrition rates of RN‐to‐BSN students 12 and simultaneous pressure to rapidly build an increasingly competent nurse workforce, there is little known about what RNs expect from their RN‐to‐BSN program, and how expectations can harm or help degree advancement.…”
Section: Responding To the Rn‐to‐bsn Students Unique Needsmentioning
confidence: 99%